PERLINDUNGAN HUKUM TERHADAP KRIMINALISASI BAGI PROFESI KURATOR DAN PENGURUS BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU - Hendra Apriyanto; Mona Wulandari (LPPM STIH Awang Long, 2025)
A curator who has many duties and authorities in carrying out his duties during the bankruptcy process will certainly encounter many problems or obstacles that must be overcome, however, even though the duties and authorities granted by the Law are quite broad, in practice, not a few curators and administrators experience obstacles in carrying out their duties and authorities. Almost recently it was also known that the curator had been sued in court by the bankrupt debtor where the bankrupt debtor thought what the curator had done was wrong and was considered to have stolen or embezzled the bankrupt debtor's assets, in this case what often happens is that there is no protection for the curator in carrying out his duties. The type of research used in this writing is normative legal research. With the existence of reports that seem forced and also fabricated, until now it can still be accepted by the police so that it seems as if the curator is a suspect who committed embezzlement because he made a sale without the agreement of the debtor, even though this is a series of stages in bankruptcy. So in this case it is known that this criminalization may actually be due to a lack of understanding by law enforcement in carrying out their duties. Therefore, legal protection for curators in carrying out their duties is necessary to prevent further criminalization of curators and administrators in Indonesia. The Curator and Administrator Profession Law will establish competency standards, national licenses, codes of ethics, and independent oversight mechanisms. This law should also provide limited immunity for curators and administrators who have worked according to procedures and in good faith. This protection is crucial so they can make swift decisions without the fear of criminalization.